ANALISIS TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN ATAS DUGAAN MANIPULASI HARGA MASKER DI TOKOPEDIA BERDASARKAN UNDANG UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Alexander Arcelino Gunadi; Ariawan Gunadi (Jurnal Hukum Adigama, 2022)
The COVID-19 pandemic that is currently engulfing Indonesia has caused public health concerns.The need for masks is a major item in the face of this pandemic. Due to the high public need forhealth, business actors commit fraudulent acts for their own benefit by increasing the price of masks.Consumer protection is “a way to give consumers a protection and a guarantee of legal certainty.The problem faced is what is the responsibility of business actors and legal protection for consumersagainst alleged manipulation of mask prices at Tokopedia based on Law Number 8 of 1999concerning Consumer Protection. The research method used in writing this thesis is normativejuridical law research. The results of the study show that the responsibility of business actors relatedto this research cannot be found in violation of the UUPK and there are no provisions concerningthe obligations of business actors to maintain the exchange rate of goods in order to remain inaccordance with the conditions and quality of goods. " The responsibility of business actors alsocannot be held for a material responsibility, but only a moral responsibility can be sought.Consumer protection against the behavior of business actors in fraudulent acts to increase the priceof the masks is not maximized and requires special arrangements in relation to these problems.